Prospective comparison of 18F-NaF PET/CT versus 18F-FDG PET/CT imaging in mandibular extension of head and neck squamous cell carcinoma with dedicated analysis software and validation with surgical specimen. A preliminary study. Issue 9 (September 2017) - Lopez, Raphael; Gantet, Pierre; Salabert, Anne Sophie; Julian, Anne; Hitzel, Anne; Herbault-Barres, Beatrice; Fontan, Charlotte; Alshehri, Sarah; Payoux, Pierre
Abstract: Background: The aim of this study is to propose a new method to quantify radioactivity with PET/CT imaging in mandibular extension in head and neck squamous cell carcinoma (HNSCC), using innovative software, and to compare results with microscopic surgical specimens. Patients and methods: This prospective study enrolled 15 patients who underwent 18 F-NaF and 18 F-FDG PET/CT. We compared the delineations of bone invasions obtained with 18 F-NaF PET/CT and 18 F-FDG PET/CT with the results of histopathological analysis of mandibular resections (from right and left bone borders). A method for visualization and quantification of PET images was developed. Results: For all patients, a significant difference ( p = 0.032 for right limits and p = 0.011 for left limits) was observed between 18 F-FDG PET/CT imaging and histopathology results, and no significant difference ( p = 0.88 for right limits and p = 0.55 for left limits) was observed between 18 F-NaF PET/CT imaging and histopathology results. The right limits were less than 10 mm in 93% of patients, and the left limits were less than 10 mm in 86% of patients. Conclusions: The dedicated software enabled the objective delineation of radioactivity within the bone. We can confirm that 18 F-NaF is a precise and specific bone marker for the assessment of intraosseous mandibular extensions of head and neck cancers. Clinical question/level of evidence: Therapeutic, III.